An Evaluation of ‘Get Smart’ English Language Textbook from the Perspectives of English Teachers - Takal, Ghazi Mohammad; Planisamay, Thilashiny; Ibrahim Gani, Nur Anisa Binti; Peter, Clara Vellangani; Rahmat, Abdul (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
This study aimed to evaluate Get Smart year three ELT textbook. A mixed methoddesign of quantitative questionnaires and qualitative interviews was used. Thirtyeight ESL lecturers from primary schools in Malaysia have been studied for their perspectives on Get Smart textbook. The quantitative questionnaires were analyzed for descriptive statistics and interviews were analyzed thematically. The findings from both questionnaire and interviews showed that Get Smart is one of the most useful books for ELT in primary schools in Malaysia. However, there were someparts which need to be improved such as the lack of creativity in illustrations,challenging vocabulary, the social and cultural mismatch, use of difficult words ingrammar explanations, lack of sentence and paragraph structures in the writing part. These findings show that Get Smart textbook is suitable but still there are some parts that need improvement.